Cloud physics from space. (30th August 2019) - Stephens, Graeme L.; Christensen, Matthew; Andrews, Timothy; Haywood, James; Malavelle, Florent F.; Suzuki, Kentaroh; Jing, Xianwen; Lebsock, Mathew; Li, Jui‐Lin F.; Takahashi, Hanii; Sy, Ousmane
Abstract: A review of the progression of cloud physics from a subdiscipline of meteorology into the global science it is today is described. The discussion briefly touches on the important post‐war contributions of three key individuals who were instrumental in developing cloud physics into a global science. These contributions came on the heels of the post‐war weather modification efforts that influenced much of the early development of cloud physics. The review is centred on the properties of warm clouds primarily to limit the scope of the article and the connection between the early contributions to cloud physics and the current vexing problem of aerosol effects on cloud albedo is underlined. Progress toward estimating cloud properties from space and insights on warm cloud processes are described. Measurements of selected cloud properties, such as cloud liquid water path are now mature enough that multi‐decadal time series of these properties exist and this climatology is used to compare to analogous low‐cloud properties taken from global climate models. The too‐wet (and thus too bright) and the too‐dreary biases of models are called out underscoring the challenges we still face in representing warm clouds in Earth system models. We also provide strategies for using observations to constrain the indirect radiative forcing of the climate system. Abstract : These are different views of ship tracks – a phenomena that expresses the effects of aerosol on low clouds, a topic explored in the article. The lower image, more grainy, is a more historical view of ship tracks from Apollo‐Soyuz on 16 July 1975 at 2221 GMT obtained from Porch et al . (1990). This image emphasizes that more is going on than simply brightening the cloud locally, with regions of suppressed albedo and mesoscale process at play. Adding aerosol to clouds does not always result in an increase in the albedo of cloud fields.